Investigation of biochemical composition of adrenal gland tumors by means of FTIR - Dudala, Joanna; Białas, Magdalena B.; Szczerbowska-Boruchowska, Magdalena; Bereza-Buziak, Monika; Budzynski, Andrzej; Hubalewska-Dydejczyk, Alicja; Kolodziej, Maciej; Pedziwiatr, Michal; Lankosz, Marek (Polish Journal of Pathology, 2016)
The application of Fourier transform infrared (FTIR) microspectroscopy for the analysis of biomolecular composition of adrenal gland tumors is described. Samples were taken intraoperatively from three types of adrenal lesions: adrenal adenoma (ACA), adrenal cortical hyperplasia (ACH), both derived from adrenal cortical cells, and pheochromocytoma (Ph) derived from chromaffin cells of the adrenal medulla. The specimens were cryo-sectioned and freeze-dried. Since the investigated lesions originated from different cell types, it was predictable that they might differ in biomolecular composition. The experimental results were used to determine which absorption bands differentiate the analyzed samples the most. The main difference was observed in the lipid functional groups. The experimental results indicated that the level of lipids was higher in both the adenoma and the hyperplasia samples compared to pheochromocytomas. In contrast, the level of proteins was higher in the pheochromocytomas. Furthermore, differences within the range of nucleic acids and carbohydrates were observed in the studied adrenal gland tumor types.